THE EFFECT OF DIFFERENT FEEDING ON GROWTH AND COLOR OF GUPPY FISH (Poecilia reticulata) - Septiyan, Rahmat; Putra, Iskandar; ', Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from April 2017 to Mei 2017, for 30 days in Aquaculture Technology Laboratory of Fisheries Faculty and Marine Sciences, University of Riau Pekanbaru. This study aimed to determine the effect of type of feeding is best to fish growth and pigmentation of guppy. The method used in this study was a laboratory-scale experimental methods with experimental design completely randomized design (CRD) with four treatments were given treatment level is P1 = Tubifex sp, Moina sp = P2, and P3 = artificial Pellets added carrot flour P4 = ornamental fish pellet. The best result was treatment P1 treatment using feed Tubifex sp absolute weight of 0,36 grams, a length of 0,59 cm absolute, and body color Guppy 4,86 scorKeyword : Guppy (Poecilia reticulata), feed,pigmentation